Kajian Perubahan Morfologi Kampung Condet Sebagai Kawasan Cagar Budaya dan Buah-buahan - Emmilia Sandy Leonita; Parfi Khadiyanto (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
The existence of the city related to the history of developments, current conditions, as well as the image of the city in the future. As part of the history, Kampung Condet, located in Kramat Jati, East Jakarta, was designated as the cultural and lands heritage area in accordance with Governor Decree No. D.I-7903/a/30/75. The occurrence of urbanization in Jakarta affecting Kampung Condet. Now, Kampung Condet has experienced numerous changes that also eliminate the identity of the cultural and land heritage area. The developments change the morphology of Kampung Condet. Based on these problems, this research aims to identify the morphological changes that occur in 2004 to 2016. This research uses qualitative descriptive spatial methods with five stages, i.e. identify Kampung Condet’s condition as thecultural and land heritage area, identify the figure ground, identifies the linkage, identify the place, and analyze the changing shape of morphology at 2004 to 2016. The results showed themorphology in Condet changing from of linear in 2004 into form of an octopus in 2016. Changes in the morphology due to land use change amounted to 36.87%. Land use in 2016 developed following the network approaching urban areas.